THE EFFECT OF CITY PARKS VEGETATION TO MEDAN CITY TEMPERATURE DECREASE - Raissa Iskandar, Paramasatya
Medan City experienced a temperature increase from 22.9°C in 2000 to 27°C in 2019 due to rapid population growth. City parks, as green areas in urban environments, play a significant ecological role in maintaining biodiversity and can help regulate temperatures. Each city park has a different composition of plant species and environmental characteristics, such as the presence of water bodies. Therefore, research on the function of city parks is necessary to understand how vegetation can lower urban temperatures.